2015
DOI: 10.1038/srep09835
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a native avirulent strain of Streptococcus suis serotype 2: a perspective for vaccine development

Abstract: Streptococcus suis, an emerging infectious pathogen, is the cause of two large-scale outbreaks of human streptococcal toxic shock syndrome in China, and has attracted much attention from the scientific community. The genetic basis of its pathogenesis remains enigmatic, and no effective prevention measures have been established. To better understand the virulence differentiation of S. suis and develop a promising vaccine, we isolated and sequenced a native avirulent S. suis strain (05HAS68). Animal experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
20
1
Order By: Relevance
“…We identified 2,221 CDSs in NSUI002. This is a slightly higher number than found in the very recently finished genome of avirulent ST28 Chinese strain 05HAS68 (2,009 CDSs) [ 13 ]. Most other closed S .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We identified 2,221 CDSs in NSUI002. This is a slightly higher number than found in the very recently finished genome of avirulent ST28 Chinese strain 05HAS68 (2,009 CDSs) [ 13 ]. Most other closed S .…”
Section: Resultsmentioning
confidence: 87%
“…suis strain 1330 was avirulent in both mice and swine [ 12 ]. More recently, it was shown that an ST28 strain isolated from the tonsils of an asymptomatic pig in China had very low virulence in a swine model of infection [ 13 ]. However, ST28 strains are often isolated from diseased swine in China and Japan [ 14 16 ], and at least four human ST28 cases have been reported in Thailand and Japan [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of the highly dynamic nature of bacterial genomes is frequent genomic rearrangements. Large inversions across the replication axis, deletions and insertions have been observed in S. pneumoniae (Camilli et al, 2011;Williams et al, 2012), S. suis (Yao et al, 2015;Athey et al, 2015), S. pyogenes (Hamada, Kawabata, and Nakagawa, 2015). The inversions have been suggested to rebalance the chromosomal architecture affected by insertions of large DNA segments (Camilli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines under development are expected to reduce mortality and clinical manifestations of S. suis systemic disease. In a previous experimental study, a native avirulent S. suis strain of serotype 2 isolated from the tonsil of a healthy pig was shown to provide complete protection against a lethal homologous S. suis serotype 2 challenge in piglets [21], which has implications for the development of an efficacious vaccine to fight this important pathogen. Similarly, a good protection was also observed in mice and swine when using another live avirulent S. suis type 2 strain (#1330), which was first isolated from the lung of a pig with pneumonia [32].…”
Section: Discussionmentioning
confidence: 97%
“…The type IV secretion system (T4SS) encoded at the 5' end of SsPI-1 can not only mediate the conjugal transfer of SsPI-1 [15], but also deliver effectors directly into the host cell, thus causing substantial tissue damage [20]. Furthermore, comparative genomics analyses revealed the complete absence of SsPI-1 in a native avirulent strain 05HAS68, but this strain contains instead, a novel ~113 kb metabolic island in the corresponding position of the genome [21], underscoring again the critical role of SsPI-1 in the pathogenesis of S. suis.…”
Section: Discussionmentioning
confidence: 99%